Revolusi Ekonomi Umat dengan Fintech Syariah: Analisis dan Peluang - Ahmad Munir Hamid; Nurwinsyah Rohmaningtyas (ADILLA : Jurnal Ilmiah Ekonomi Syari'ah, 2024)
This research explains the opportunities that Indonesia has as one of the countries with the largest number of sharia fintech in the world, which reached 61 companies in 2021. The study also discusses regulations and business models that can support the development of sharia fintech in Indonesia, given the importance of a clear legal framework to maintain trust and compliance with sharia principles. In addition, the analysis of public interest in sharia fintech shows that there is great potential for further development, although there are still challenges that need to be overcome such as financial literacy and access to technology. Overall, this study concludes that sharia fintech has great potential to support the economic empowerment of the people through inclusive and sharia-compliant financial services. However, to realize this potential, collaboration between the government, industry players, and the community is needed to create an ecosystem that is conducive to the development of sharia fintech.